2018
DOI: 10.1016/j.foreco.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the causes and temporal distribution of tree mortality in Central Amazonia

Abstract: Tree mortality is a critical process in forest ecosystems, as it influences floristic composition, structure, dynamics, carbon storage, and forest nutrient cycling. However, the mechanisms behind tree death in tropical regions are still poorly characterized. This lack of information is mainly because tree mortality data come from long-interval inventories and studies that measured tree death seasonally are scarce. Here we offer novel insights into the power of fine temporal scale observations and we use a natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 77 publications
1
44
0
1
Order By: Relevance
“…Nevertheless, direct observations of the exact processes and conditions that cause tree death are extremely rare (but see refs. 13,14 ), making information from standardised, long-term forest monitoring plots the principal means we have to derive large-scale geographical patterns and differentiate among the potential drivers of tree mortality. In plots, the inferred mode of death (standing vs. broken or uprooted) can be used to provide the basis for understanding the causes of death.…”
mentioning
confidence: 99%
“…Nevertheless, direct observations of the exact processes and conditions that cause tree death are extremely rare (but see refs. 13,14 ), making information from standardised, long-term forest monitoring plots the principal means we have to derive large-scale geographical patterns and differentiate among the potential drivers of tree mortality. In plots, the inferred mode of death (standing vs. broken or uprooted) can be used to provide the basis for understanding the causes of death.…”
mentioning
confidence: 99%
“…Smith et al , ; Sherman et al , ; Amir & Duke, ), and we expect that it will prove to be a similarly important mechanism of tree mortality at other tropical forest sites (Anderson, ; Magnusson et al , ). The only other quantitative assessment of lightning‐caused mortality in a terrestrial tropical forest found a similar contribution to total tree mortality (Fontes et al , ). Specifically, bimonthly assessments of 5808 trees near Manaus in central Amazonia for one year showed that 4.5% of deaths of trees > 10 cm in diameter were due to lightning (Fontes et al , ), which was equal to our finding of 4.5% for this size class.…”
Section: Discussionmentioning
confidence: 85%
“…The only other quantitative assessment of lightning‐caused mortality in a terrestrial tropical forest found a similar contribution to total tree mortality (Fontes et al , ). Specifically, bimonthly assessments of 5808 trees near Manaus in central Amazonia for one year showed that 4.5% of deaths of trees > 10 cm in diameter were due to lightning (Fontes et al , ), which was equal to our finding of 4.5% for this size class. Moreover, lightning frequency is high in most tropical forests; 68% of evergreen broadleaf tropical forests experience ≥ 50% of the lightning frequency recorded for BCI (Cecil et al , ; Friedl & Sulla‐Menashe, ).…”
Section: Discussionmentioning
confidence: 85%
“…In addition, the increased presence of necromass in later stages of decomposition indicates that tree mortality may have occurred at more distant times. This fact highlights the need to carry out more frequent forest inventories and to monitor the phytosanitary conditions of the trees while alive to determine more precisely when a tree dies [54].…”
Section: Discussionmentioning
confidence: 99%